RNA-directed DNA methylation efficiency depends on trigger and target sequence identity - Dalakouras, Athanasios; Dadami, Elena; Wassenegger, Michèle; Krczal, Gabi; Wassenegger, Michael (The plant journal, 2016)
RNA-directed DNA methylation (RdDM) in plants has been extensively studied, but the RNA molecules guiding the RdDM machinery to their targets are still to be characterized. It is unclear whether these molecules require full complementarity with their target. In this study, we have generated Nicotiana tabacum (Nt) plants carrying an infectious tomato apical stunt viroid (TASVd) transgene (Nt-TASVd) and a non-infectious potato spindle tuber viroid (PSTVd) transgene (Nt-SB2). The two viroid sequences exhibit 81% sequence identity. Nt-TASVd and Nt-SB2 plants were genetically crossed. In the progeny plants (Nt-SB2/TASVd), deep sequencing of small RNAs (sRNAs) showed that TASVd infection was associated with the accumulation of abundant small interfering RNAs (siRNAs) that mapped along the entire TASVd but only partially matched the SB2 transgene. TASVd siRNAs efficiently targeted SB2 RNA for degradation, but no transitivity was detectable. Bisulfite sequencing in the Nt-SB2/TASVd plants revealed that the TASVd transgene was targeted for dense cis-RdDM along its entire sequence. In the same plants, the SB2 transgene was targeted for trans-RdDM. The SB2 methylation pattern, however, was weak and heterogeneous, pointing to a positive correlation between trigger-target sequence identity and RdDM efficiency. Importantly, trans-RdDM on SB2 was also detected at sites where no homologous siRNAs were detected. Our data indicate that RdDM efficiency depends on the trigger-target sequence identity, and is not restricted to siRNA occupancy. These findings support recent data suggesting that RNAs with sizes longer than 24 nt (>24-nt RNAs) trigger RdDM.
Gesehen am 06.05.2020